Recent progress in theory and observational study of dust grain alignment and rotational disruption in star-forming regions - Tram, Le Ngoc; Hoang, Thiem (Frontiers in Astronomy and Space Sciences, 2022)
Modern understanding of dust astrophysics reveals that RAdiative Torques (RATs) arising from the radiation-dust interaction can induce two fundamental effects, including grain alignment and rotational disruption. Here we review the recent progress in the theoretical development and observational testing of these effects using dust polarization observed toward star-forming regions (SFRs). We first review the basic theory of the RAT alignment and RAT disruption, which are referred to as RAT-A and RAT-D effects, respectively. We then briefly describe the numerical method we use to model polarized thermal dust emission by accounting for both RAT-A and RAT-D and theoretical predictions of dust polarization for observations. Next, we review our observational efforts to search for observational evidence of the RAT-A and RAT-D effects using thermal dust polarization toward SFRs. Finally, we discuss magnetic fields inferred from dust polarization observed toward these SFRs and implications of the RAT paradigm for different astrophysical conditions, including protostellar environments, dust evolution, and time-domain astrophysics.